Fuzzy analytic hierarchy process to study the impacts of Open Distance Learning on UiTM Perlis students / Adriana Nazihah Cha Ariff and Norpah Mahat - Cha Ariff, Adriana Nazihah; Mahat, Norpah (College of Computing, Informatics and Media, UiTM Perlis, 2023)
On March 18th 2020, the Malaysian government imposed a Movement Control Order (MCO) due to the high infection rates of COVID-19. This new disease had a significant impact on several aspects namely economic, educational and social aspects. During the lockdown, the entire education system, from primary to higher education, collapsed not only in Malaysia but worldwide. Teaching and learning methods have also been changed from traditional methods to online distance learning in order to reduce the spread of the Corona virus. Although distance education is convenient, there are some obstacles that students have to overcome. The main objective of the study is to identify the main impacts of open distance learning (ODL) on UiTM Perlis students using Fuzzy Analytic Hierarchy Process. Therefore, the use of Fuzzy Analytic Hierarchy Process was proposed in this study. Fuzzy Analytic Hierarchy Process (FAHP) is a method of Analytic Hierarchy Process (AHP) developed using fuzzy logic theory. This study found that the greatest impact of ODL on UiTM Perlis students is time spent learning, followed by sleep patterns, student performance, engagement to learn and mental health.The results of the study show that the greatest impact of Open Distance Learning (ODL) on UiTM Perlis students is the time they spend learning.